Winning Turkey : how America, Europe, and Turkey can revive a fading partnership - Gordon, Philip H., 1962- (Brookings Institution Press, 2008)
"Explains current situation and designs a plan to ease tensions in Turkey. Proposes a 'grand bargain' between Turkey and the Kurds, advocating greater support for increased liberalism and democracy, renewed European and Turkish commitment to promote EU membership, a historic compromise with Armenia, and greater Western engagement with Turkish Cypriots"--Provided by publisher